"أداء الموظف العام في الجزائر بين الكفاءة العلمية و الخبرة المهنية - بلدية تقرت " - عرعار, أمينة (جامعة الوادي university el-oued)
" ان الأداء من النشاطات المهمة و الرئيسية للمؤسسات العمومية في الوقت الراهن ، حيث يساهم بشكل كبير في تحقيق أهداف المؤسسة، ومن اجل الرفع من مستوى تقديم الخدمات إلى أقصى حد وبالتالي ضمان الجودة وكسب رضا المواطنين . وتعتبر البلدية كغيرها من المؤسسات العمومية التي تولي أهمية بالغة للأداء الوظيفي، مما جعلها تركز على مواردها البشرية الحالية و المستقبلية لكونها السبيل المؤدي إلى تحقيق أداء عال وراق داخل المنظمة و ذلك بالاعتماد على الكفاءات العلمية و الخبرة المهنية قبل و بعد الالتحاق بالوظيفة، وقد توصلنا من خلال الدراسة إلى ان هذان العنصران يعتبران القاعدة الرئيسية للأداء الموظف العام بالإدارة العمومية . " Performance is one of the most important and important activities of public institutions at the present time. It contributes significantly to the achievement of the objectives of the institution, in order to maximize the level of service delivery and thus ensure quality and gain the satisfaction of citizens. The Municipality, like other public institutions, attaches great importance to job performance, which has focused on its current and future human resources as a way to achieve high performance within the organization based on scientific competencies and professional experience before and after joining the job. During the study that these two elements are considered the main rule of performance public administration employee. " "
م.س.ع.19
Keywords: الاداء، الموظف العام، الخبرة المهنية، الكفاءة العلمية; Performance, general employee, professional experience, scientific competence